HUMANITIES MEANINGS IN TULUS' TEH HIJAU: AN INTEGRATED SEMIOTIC ANALYSIS OF ROLAND BARTHES AND CHARLES SANDERS PEIRCE - RR Roosita Cindrakasih; Adityo Fajar; Sultan Himawan; Agung Rahardjo; Marlina Rahmi Shinta P (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
His study aims to examine the denotative, connotative, and mythical meanings embedded in Teh Hijau, a song by Tulus, through a humanities perspective. The research employed a descriptive qualitative method using Roland Barthes' semiotic analysis, complemented by Charles Sanders Peirce's classification of signs. The data consisted of the song lyrics and their production context, which were analyzed to identify signification at the levels of denotation, connotation, and myth. The findings reveal that the image of a cup of green tea symbolizes a simple yet meaningful source of emotional stability amid feelings of emptiness and uncertainty. The contrast between the song's cheerful musical arrangement and reflective lyrics reinforces the idea that emotional healing does not always appear dramatic. At the mythical level, the song challenges the cultural expectation that sadness must be resolved immediately and instead promotes gradual self-acceptance. From a humanities perspective, Teh Hijau reflects a shift in how urban Indonesian youth understand happiness and emotional recovery as quiet, personal processes rather than achievements that must be publicly displayed